CATALITYC CONVERTER JENIS LUBANG HORIZONTAL UNTUK MENGURANGI EMISI KENDARAAN BERMOTOR - Ali Mokhtar (Jurnal Gamma, 2010)
Degradation of gas emission rate throw away is influenced by channel form and streamdistribution in channel of catalytic converter. From recommended model in the research of firstyear, that is model 1 and model 4 showing result of good spreading. From result of data analysiswith recommended model in research of first year indicate that the degradation of biggest emissionon the 4 model, especially for the rate of emission of HC equal to 21,4% and rate of CO equal to24,6%, while for model 1 as a whole still under model 4.